2014
DOI: 10.1039/c4fo00316k
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dose on the bioavailability of coffee chlorogenic acids in humans

Abstract: Single servings of coffee beverage containing low (412 µmol), medium (635 µmol) and high (795 µmol) amounts of chlorogenic acids were administered to eleven healthy volunteers in a double-blind randomised controlled trial. Analysis of plasma and urine collected for 24-h revealed the presence of 12 metabolites in plasma and 16 metabolites in urine, principally in the form of sulphates, and to a lesser extent glucuronides of caffeic, ferulic, dihydrocaffeic and dihydroferulic acids, as well as intact feruloylqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
79
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 30 publications
7
79
2
2
Order By: Relevance
“…participants a single serving of a coffee beverage fortified with CHL, the serving consisted of low (412 μmol), CHL that was found the MC concentrate that represents a sensible portion to consume, rather than an artificially 309 derived concentration used previously [34,35]. In support of this, a previous study using comparable…”
mentioning
confidence: 80%
“…participants a single serving of a coffee beverage fortified with CHL, the serving consisted of low (412 μmol), CHL that was found the MC concentrate that represents a sensible portion to consume, rather than an artificially 309 derived concentration used previously [34,35]. In support of this, a previous study using comparable…”
mentioning
confidence: 80%
“…62 In comparison, a single serving of espresso coffee provides between 24 -422 mg of CGA and 51 -322 of caffeine, corresponding to approximately 6 -12 mM CGA and 8 -16 mM caffeine depending on the type of roast and the volume consumed. 63 In the studies about the bioavailability of coffee phytochemicals, plasma levels up 1.5 µM CGA and 13 µM methylxanthines have been reported after the intake of coffee beverages providing 2 -4 mM CGA and 1 mM methylxanthines, 19,21,23 with higher plasma concentrations of CGA (up to 10 µM) reported after the intake of roasted coffee. Based on previous results, 40,39 the highest dose tested of phenolic extracts was 100 µg/mL in the present study, corresponded to approximately 200 µM CGA and 50 µM methylxanthines; however, the doses tested for phenolic extracts ≤ 1 µg/mL would be within the physiological range for CGA (equivalent to approximately ≤ 2 µM CGA), while all tested concentrations would be physiological for methylxanthines.…”
Section: Effect On Fibrinogen Bindingmentioning
confidence: 99%
“…57 On the contrary, concentrations of at least 100 µM were necessary to inhibit the expression of TRAP-and ADPinduced P-selectin by the early metabolites CA and FA, and 5-CQA, respectively, 42,58 while the 12 results of this study showed a significant decrease of ADP-induced P-selectin expression at noticeably lower concentrations (20, 10 and 1 µM for CA, FA and 5-CQA, respectively), indicating that the colonic metabolites may have an even stronger effect on platelet function than their phenolic precursors. Early metabolites from CGA appear at 1 -2 h after coffee intake, and have a short life time of approximately 30 min, 21,59 whereas DHCA and DHFA appear in the circulation 5 -10 h after consumption and their life time is between 0.7 and 2.1 h. 19 A longer circulation time of colonic metabolites, together their higher effect on platelet function, suggest that these colonic metabolites may be the main contributors to the beneficial effect of CGA-rich foods on human platelet function. The differences in efficacy could relate to their molecular structure.…”
Section: Effect On Fibrinogen Bindingmentioning
confidence: 99%
See 2 more Smart Citations